Brattle Street Church, the City Hotel and the City Hotel Stable, ca. 1865 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Street-level view northwest of the City Hotel and the City Hotel Stable, located at 55 Brattle Street. The facade of the hotel faces south towards Brattle Street. The sign for the City Hotel Stable stretches across the alley along the hotel's east elevation, between Brattle Street to the south and Elm Street to the north. Several carriages are parked in the alley. The Brattle Street Church, located to the west of the City Hotel, is visible along the left side of the photograph. Four men pose in front of the hotel for the photographer. Signage and wrought iron railing adorns the hotel's facade. 6 15/16 in diameter (image is round); 7 5/8 x 8 3/8 overall Albumen prints